-6(x+2)+15=-4x-7

Simple and best practice solution for -6(x+2)+15=-4x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+2)+15=-4x-7 equation:


Simplifying
-6(x + 2) + 15 = -4x + -7

Reorder the terms:
-6(2 + x) + 15 = -4x + -7
(2 * -6 + x * -6) + 15 = -4x + -7
(-12 + -6x) + 15 = -4x + -7

Reorder the terms:
-12 + 15 + -6x = -4x + -7

Combine like terms: -12 + 15 = 3
3 + -6x = -4x + -7

Reorder the terms:
3 + -6x = -7 + -4x

Solving
3 + -6x = -7 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
3 + -6x + 4x = -7 + -4x + 4x

Combine like terms: -6x + 4x = -2x
3 + -2x = -7 + -4x + 4x

Combine like terms: -4x + 4x = 0
3 + -2x = -7 + 0
3 + -2x = -7

Add '-3' to each side of the equation.
3 + -3 + -2x = -7 + -3

Combine like terms: 3 + -3 = 0
0 + -2x = -7 + -3
-2x = -7 + -3

Combine like terms: -7 + -3 = -10
-2x = -10

Divide each side by '-2'.
x = 5

Simplifying
x = 5

See similar equations:

| 3.2=4.4-0.3x | | (7x+1)+(13x+9)=90 | | 2(4-3x)-10=2x-74 | | 4x^3-9x^2-2=0 | | 13y-1.8=-5y+3.6 | | 4(5c+1)-26=17c+2 | | 33t=-46 | | X*.6=25 | | 5√6/4√50 | | 3x-8=4(x+4) | | 3m-7+m+23= | | 3x+29=6x+8 | | 4(x-3)=x-12 | | 8x%3-2x%4=-14 | | 4x-27andX+39= | | -11n-7=11 | | k/6-7=-4 | | 2(2x+5)+2x=250 | | 6x-15=5x+6-2x | | 1/2in(e^6) | | (5√6)/(4√50) | | (12n+99)+(8n+8)= | | 20n-16=0 | | 35x^3+63x^5+21x^6= | | a/a+4=3-4/a+4 | | r/6=-9+3 | | 2(3x+2)=2(x-4) | | 7x+70=x+50 | | f(x)=3x^4-8x^3+5 | | X-(13)=21 | | 7(2x-7)-5=14x-54 | | x+50=4x+20 |

Equations solver categories